SURVEI KELINCAHAN DAN KECEPATAN PEMAIN FUTSAL PADA EKSTRAKURIKULER SMA NEGERI 7 BENGKULU SELATAN - Putra, H.; Syaputra, R.; Sembiring, L. T.; Sumantri, Ajis (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
This study aims to determine the agility and speed of futsal players in the extracurricular of SMA Negeri 7 Bengkulu Selatan. This research uses quantitative descriptive. The method used is a survey. The population in this study were students of SMA Negeri 7 South Bengkulu, totaling 20 students. The sample used in this study were students of SMA Negeri 7 Bengkulu Selatan. The test instrument used was the zig-zag run agility test, and the speed of running 50 meters. Data using descriptive analysis techniques which are outlined in percentage form. The results showed that the ability of futsal players in the extracurricular of SMA Negeri 7 Bengkulu Selatan with the results for the agility test, the highest frequency category in the